FRAMING ANALYSIS :THE DIFFERENCES OF KOMPAS' FRAME AND UTUSAN MALAYSIA'S FRAME REGARDING THE AMBALAT CASE - Rika Apriani, - (2008)
The present study is entitled "Framing Analysis: the Differences of Kompas' Frame and Utusan Malaysia's Frame regarding the Ambalat Case". This study aims to investigate the differences in frames of Kompas and Utusan Malaysia with regard to the Ambalat case and to examine the ideology behind the differences. This study employs CDA as the analytical framework. Purposive sampling was used in collecting the data. The data included four articles taken from Kompas and Utusan Malaysia. The data are analyzed using three stages of analysis whose approach proposed by Fairclough (1995), namely the description stages, the interpretation stages, and the explanation stages. This study identifies the framing elements, whose elements proposed by Entman (cited in Eriyanto, 2002). This study focuses on the analysis of thematization, transitivity, and evaluations. The finding of this study shows that Kompas and Utusan Malaysia have different frames in presenting the Ambalat case. They identify different problem and different cause of the problem, make different moral evaluation, and give different treatment recommendations to solve the case. It reveals that the respective media involve their nationalism in reporting the Ambalat case.